Corporate governance and corporate profitability of listed hotels & travels companies in Sri Lanka: moderating role pf finance decision - Anandasayanan, S.; Velnampy, T. (University of Jaffna, 2017)
Strong corporate governance is necessary for all the business organizations it plays an important role in the management or organizations in both developed and developing countries. The purpose of the study is to find out the moderating role of financing decisions on corporate governance and corporate profitability of listed hotels & travels companies listed in Colombo stock exchange. A survey was carried out on all the 19 companies during the period 2011 to 2015. The moderating effects of financing decisions on the relationship between corporate governance and corporate profitability were tested. In this study board size and board composition, were considered as independent variables and return and total Assets was used profitability measurement. Further debt to equity ratio was used represent the financing decision as moderating variable. Hypotheses were tested using regression analysis. Descriptive statistics were computed for the hotels and travels companies and the main characteristics of the study variables. The findings revealed that the influence of corporate governance and corporate profitability was statically significant. Debt to equity ratio also significantly impact on corporate profitability. There was a significantly moderating effect of financing decision on the association between corporate governance and corporate profitability. The study brings out an increased understanding that the combinative effect of the study variables is greater than the individual effects therefore organizations can enhance their performance by implementing good corporate governance practices.
Keywords: Corporate Governance; Corporate profitability; Financing Decision